2019
DOI: 10.1126/sciadv.aav9824
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mtDNA copy number ameliorates the pathological consequences of a heteroplasmic mtDNA mutation in the mouse

Abstract: Heteroplasmic mtDNA mutations typically act in a recessive way and cause mitochondrial disease only if present above a certain threshold level. We have experimentally investigated to what extent the absolute levels of wild-type (WT) mtDNA influence disease manifestations by manipulating TFAM levels in mice with a heteroplasmic mtDNA mutation in the tRNAAla gene. Increase of total mtDNA levels ameliorated pathology in multiple tissues, although the levels of heteroplasmy remained the same. A reduction in mtDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
111
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 49 publications
14
111
3
Order By: Relevance
“…The oxidative stress response causes damage to mtDNA replication enzymes and thus aggravates the decrease in mtDNA-CN further [78]. In pressure-overload-induced HF mice, increased mtDNA-CN induced by the overexpression of Twinkle or TFAM-alleviated fibrosis of the left ventricle, limited mitochondrial oxidative stress, and improved cardiac function [79,80]. One study observed an inverse association between mtDNA-CN and coronary artery disease in a Chinese population, especially among smokers, and found an inverse correlation between mtDNA-CN and ROS production.…”
Section: Oxidative Damage To Mitochondrial Dna Copy Numbermentioning
confidence: 99%
“…The oxidative stress response causes damage to mtDNA replication enzymes and thus aggravates the decrease in mtDNA-CN further [78]. In pressure-overload-induced HF mice, increased mtDNA-CN induced by the overexpression of Twinkle or TFAM-alleviated fibrosis of the left ventricle, limited mitochondrial oxidative stress, and improved cardiac function [79,80]. One study observed an inverse association between mtDNA-CN and coronary artery disease in a Chinese population, especially among smokers, and found an inverse correlation between mtDNA-CN and ROS production.…”
Section: Oxidative Damage To Mitochondrial Dna Copy Numbermentioning
confidence: 99%
“…A high level of neocortical superoxide was seen in the double mutants compared with the single mutants. Simple increase in the copy number of mtDNA (achieved by manipulating TFAM expression) reduces the severity of pathology in a heteroplasmic mouse bearing a mutation in mt tRNA Ala although the levels of heteroplasmy remained the same [ 284 ]. Conversely, a reduction in mtDNA levels worsened the phenotype in postmitotic tissues, such as heart, although enhanced clonal expansion and selective elimination of mutated mtDNA lead to a beneficial effect in rapidly proliferating tissues, such as colon.…”
Section: Genetics Of Mitochondrial Dnamentioning
confidence: 99%
“…This scheme experienced another level of complexity, due to the existence of multiple mitochondria per cell, the mtDNAs of which may vary in sequence (heteroplasmy). Specifically, heteroplasmy patterns and their phenotypic consequences notably differs between dividing (mitotic) and post-mitotic tissues (Kowald and Kirkwood, 2013;Filograna et al, 2019). Therefore, mitochondrial phenotypic implications should be considered not only at the level of the organism which has been widely discussed in the past (Meiklejohn et al, 2007;Levin et al, 2014), but also at the level of the cell, and even in the single mitochondrion (Figure 1).…”
Section: Selection Acts On the Phenotype-the Various Levels Of Mitochmentioning
confidence: 99%